(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The objective of the research was to establish the influence of socio-emotional skills for the reduction of social anxiety in university students. Quantitative methodology was used to collect the information data, using the survey as a technique and the questionnaire as an instrument. The population consisted of 600 university students, divided into two groups, the control group was considered 300 students and the experimental group was considered 300 students. The socio-emotional skills intervention program decreases levels of social anxiety, reduces the levels of anxiety that is generated in the interaction with people who exercise authority, in the anxiety in the interaction with the opposite sex; Likewise, it decreases in the assertive expression of annoyance, decreases anxiety due to displeasure or anger. making a fool of yourself or making a fool of yourself and decreased anxiety about interacting with strangers; Therefore, socio-emotional skills facilitate relationships and promote emotional balance, enabling the ability to recognize, understand and manage their emotions.